1996
DOI: 10.1086/310256
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 800 Hz Quasi-periodic Oscillations in 4U 1608−52

Abstract: We present results of RXTE observations of the low-mass X-ray binary and atoll source 4U 1608−52 made over 9 days during the decline of an X-ray intensity outburst in March 1996. A fast-timing analysis shows a strong and narrow quasi periodic oscillation (QPO) peak at frequencies between 850 and 890 Hz on March 3 and 6, and a broad peak around 690 Hz on March 9.Observations on March 12 show no significant signal. On March 3, the X-ray spectrum of the QPO is quite hard; its strength increases steadily from 5 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
105
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 14 publications
15
105
1
1
Order By: Relevance
“…The burst emission dominates in the soft X-ray band while the QPO modulated photons have a harder spectrum (Berger et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The burst emission dominates in the soft X-ray band while the QPO modulated photons have a harder spectrum (Berger et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the fractional rms amplitude of the variability (at least at frequencies ∼Hz or higher) increases with energy for accreting NS LMXBs (see e.g. Lewin et al 1992;Berger et al 1996;Zhang et al 1996;Homan et al 1999). The same is true for the Very Low Frequency Noise (VLFN) in 4U1608-52 and 4U1636-536 at frequencies comparable to the mQPO frequency.…”
Section: Discussionmentioning
confidence: 99%
“…We have selected 4U 1608-522 because in a rather limited data set, a loss of coherence of the lower QPO was reported by Berger et al (1996) and Barret et al (2005a). The choice of 4U 1735-44 is motivated by the fact that not much is known about its kilo-Hz QPOs (see however Wijnands et al 1998 andFord et al 1998), while the source has been rather extensively observed with RXTE.…”
Section: Introductionmentioning
confidence: 99%